Agile Supply Chain Management in Multinational Corporations: Opportunities and Barriers - Pavel V.Zhukov; Alexander A.Silvanskiy; Kirill Y.Mukhin; Olga L.Domnina (International Journal of Supply Chain Management, 2019)
The purpose of our research is to study new opportunities in agile supply chain management, identify barriers to agile supply chain management, develop a methodology to overcome these barriers and make proposals for agile supply chain management in multinational corporations.The study and analysis of supply chain management of multinational corporations allowed us to define the specifics of the industry using the following research methods: the choice of logistics intermediaries, forecasting (indicators, flows, etc.), nomenclature groups, risk optimization, statistical data analysis.The methods of grouping and systematizing statistical data into registries were applied to assess the business agility of supply chain management and obtain results. In addition, the expert assessment method was used to assess the agility indicators of the following companies METRO Cash & Carry, Gloria Jeans and Gazprom. Procurement (timeliness and prices), supply management, product management, finished-product output and shipment management were assessed. The calculations showed that the multinational corporations METRO Cash & Carry, Gloria Jeans and Gazprom should continue to increase the agility of supply chain management and implement the SCM strategy, which will quickly address and mitigate supply chain disruptions. We also believe that the companies should adapt SCM in the organizational structure optimization in order to eliminate bottlenecks.